Novel Single Phase Full Bridge Inverter Formed by Floating Capacitors - Prathap Reddy Bhimireddy; Sreekanth Reddy Kondreddy; Samba Siva Reddy Beduduri (Institute of Advanced Engineering and Science, 2016)
In this paper, a new single-phase bridge inverter is described which can generate a more steps of voltage levels with reduced number of switches, gate driver circuits and diodes as compare to normal multilevel inverter. Another feature of this inverter is its ability to prodeuce the voltages from a single dc-link power supply which enables back-to-back operation of converter. The proposed method with more number of levels can improve power quality, lower switching losses and produce high quality voltage waveforms. Moreover at all load power factors the proposed method can be operated.The research of the model is done by means of computer simulation with the software MATLAB/SIMULINK. This topology has very low common mode voltage variation and dv/dt stress. Also this inverter is help full for reactive power compensation.